Wobec niepodległości. Próba rekonstrukcji wizji programowej środowiska politycznego „Głosu” w latach 1976–1980 - Brzechczyn, Krzysztof (Kolegium Europy Wschodniej / Uniwersytet Wrocławski, 2018)
The purpose of this paper is to reconstruct the ideological differences between two factions of KSS “KOR” members and collaborates, namely the group gathered around journals: “Biuletyn Informacyjny”, “Robotnik” and "Krytyka" and a group publishing “Głos”. The paper aims to reconstruct political thought presented in the “Głos”. According to the author, there were two main controversies between two groups in years 1976–1980, namely estimation of revisionism in postwar history of Poland and attitude towards gaining independence by Poland.
Keywords: opozycja demokratyczna; KSS "KOR"; Głos; myśl polityczna; Adam Michnik; Antoni Macierewicz; Jacek Kuroń; Jakub Karpiński; niepodległość; rewizjonizm